2018
DOI: 10.3126/nutaj.v5i1-2.23450
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Teacher Training: A Case of Teaching Speaking

Abstract: The present study entitled 'Transfer of Teacher Training: A Case of Teaching Speaking' aims at identifying and describing the teaching activities of trained teachers in terms of motivation, presentation, practice, methods and techniques and evaluation system of teaching and to analyze the transfer of training of trained teachers in teaching speaking skills. This research study shows that training is essential in teaching language especially speaking skills. Trained teachers in most of the cases were found succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In the present study, in terms of the transfer of knowledge, training and skills involved in the learning materials preparation, the majority of trainees (68%) expressed that they were capable of providing the training skills they obtained to their fellow colleagues to a "large extent", 20% noted that they had this competency to "some extent" while 8% opined that they were "poor" in this aspect (Figure 7). These findings are in line with those of Adhikari (2018), who found that most trainees were successful in transferring a number of training skills. Although the number of respondents who were poor in TOT is only 8%, institutions need to focus on these people and utilize the services of the in-house trained faculty to further build the capacity of their own colleagues.…”
Section: Evaluation Of Faculty Development Programmesupporting
confidence: 91%
“…In the present study, in terms of the transfer of knowledge, training and skills involved in the learning materials preparation, the majority of trainees (68%) expressed that they were capable of providing the training skills they obtained to their fellow colleagues to a "large extent", 20% noted that they had this competency to "some extent" while 8% opined that they were "poor" in this aspect (Figure 7). These findings are in line with those of Adhikari (2018), who found that most trainees were successful in transferring a number of training skills. Although the number of respondents who were poor in TOT is only 8%, institutions need to focus on these people and utilize the services of the in-house trained faculty to further build the capacity of their own colleagues.…”
Section: Evaluation Of Faculty Development Programmesupporting
confidence: 91%
“…Yet these policies are unclear on ways to ensure the transfer of training or find out the factors that promote or inhibit transfer. Among a few studies on training transfer, Adhikari (2018) exhibits transfer level in general education, and Koirala et al (2016) show trainee satisfaction of TVET instructors at the reaction level. However, these studies do not address the issues of environmental factors affecting training transfer among TVET instructors.…”
Section: Notion Of Work Environmental Factors Affecting Training Tran...mentioning
confidence: 99%